Penapisan dan Karakterisasi Bakteri Amilo-Termofilik dari Sumber Air Panas Semurup, Kerinci, Jambi - Wira Hastuti; Anthoni Agustien; - Nurmiati (Universitas Andalas, 2012)
The screening and characterization of amylo-thermophylic bacteria that produced amylase from Semurup hot spring in Kerinci, Jambi was conducted from May to July 2012. The aim of this study was to find out the isolate of amylo-thermophylic bacteria and to analyze amylase activities. This study used experimental methods. This study found 31 isolates of amylo-thermophylic bacteria with the amylolytic index more than 2. The isolate SII- 1.7 has the highest enzyme activity. The form of colony was circular margin, smooth shiny surface and pigmentation cream. The bacterium was gram negative, bacilli cell, positive catalase, non-motile, and has proteolytic and amylolytic activities.Keywords: amylolytic, bacterium, characterization, hot spring, thermophylic